Outdoor Based Ecosystem Learning during the Covid Pandemic 19 Merauke Elementary School Students - Yonarlianto Tembang; Ratna Purwanty (Universitas Pendidikan Ganesha, 2020)
Pandemic Covid-19 requires all elements of education to carry out online learning, but not all schools, especially in the Merauke district, do this because they see the readiness of students who do not have communication tools to be used as messengers in learning. This study aims to increase the activeness and learning outcomes of students in the learning ecosystem of class V students. This research is a classroom action research with collaborative research type and is carried out in two cycles consisting of planning, implementing, observing, and reflecting. The subjects in this study were 18-grade students of SD YPPK Santo Tarsisius Biankuk. The data collection techniques used were observation, interviews, documentation, and student learning evaluation tests. Based on the results of this study, it can be concluded that student learning outcomes during the Covid-19 pandemic outdoor based on ecosystem lessons increased in cycle 1 by 60.1, and in cycle II increased by 81.1, this study also increased student activity in learning at each meeting. Based on this research, it can be concluded that outdoor-based ecosystem learning can improve learning outcomes of fifth-grade students who are impacted by online learning.